Pengembangan Website Sebagai Sarana Peningkatan Promosi Pasar Tradisi Lembah Merapi Di Desa Wisata Banyubiru Kabupaten Magelang - Ustyannie, Windyaning; Sambuari , Meychel Danius Fedrix; Almuntaha, Eska; Susanti, Erma (LPPM IST AKPRIND Yogyakarta, 2022)
Banyubiru Tourism Village has a market potential that is able to attract tourists to come to the Merapi Valley Tradition Market. The market sells a variety of traditional specialties, traditional souvenirs, traditional utensils, and so on. However, in the promotional activities of this tourist village, it is still conventional and has not been touched by digital promotions, either in the form of websites or social media. This is the background for the community service program to create a website for the Merapi Valley Tradition Market in Banyubiru Tourism Village, Dukun District, Magelang Regency. The activity of making this website began with observations of the Head of RW, Head of RT and local residents to collect information about the Merapi Valley Traditional Market. After the website content components have been sufficient, proceed with the design and content of the Merapi Valley Traditional Market website. Furthermore, the implementation of website creation begins with the preparation of hosting and domains as well as the addition of SSL for website security. These components are needed so that the website can be accessed online by anyone who needs information. Hosting is a service for storing data, images, and files on a website. Domain is the website address. Additional security features SSL (Secure Socket Layer) is required to provide encryption security on the website. The process after implementation, namely uploading the website to the hosting that has been provided. The last is the handover of the website to the Management of the Merapi Valley Traditional Market. Making this website aims to make it easier for the wider community, both domestic and foreign tourists to get information about the cultural diversity in the Banyubiru Tourism Village, especially the culture in the Merapi Valley Tradition Market.